CONTROLLING RISK INSIDE MODERN GOVERNMENT: DEVELOPING INTERVAL MEASURES OF THE GRID‐GROUP DIMENSIONS FOR ASSESSING SUICIDE RISK CONTROL SYSTEMS IN THE ENGLISH AND JAPANESE PRISON SERVICES. (22nd June 2016) - NAKAMURA, AYAKO
Abstract : Mechanisms for controlling government organizations have attracted major interest from public administration researchers. Cultural theory has been used as a tool to identify the core control approaches of individual organizations. Whereas major existing studies have applied the theory based on the cultural types using nominal‐level measures, this article builds a novel set of interval measures, focusing on two fundamental factors of government control proposed by cultural theory: grid‐group dimensions. The measures are applied to assess suicide risk control systems in the English (HMPS) and Japanese prison services (JPS). The results highlight the fatalistic approach in HMPS and egalitarian approach in JPS, as well as demonstrating the structural characteristics of each risk control system beyond nominal lists of control tools.